Precursors of Viral Proteases as Distinct Drug Targets - Majerová, Taťána; Novotný, Pavel (Viruses, 2021)
Viral proteases are indispensable for successful virion maturation, thus making them a prominent drug target. Their enzyme activity is tightly spatiotemporally regulated by expression in the precursor form with little or no activity, followed by activation via autoprocessing. These cleavage events are frequently triggered upon transportation to a specific compartment inside the host cell. Typically, precursor oligomerization or the presence of a co-factor is needed for activation. A detailed understanding of these mechanisms will allow ligands with non-canonical mechanisms of action to be designed, which would specifically modulate the initial irreversible steps of viral protease autoactivation. Binding sites exclusive to the precursor, including binding sites beyond the protease domain, can be exploited. Both inhibition and up-regulation of the proteolytic activity of viral proteases can be detrimental for the virus. All these possibilities are discussed using examples of medically relevant viruses including herpesviruses, adenoviruses, retroviruses, picornaviruses, caliciviruses, togaviruses, flaviviruses, and coronaviruses.
Keywords: SARS-CoV-2; autoprocessing; virové proteasy; flaviviruses; herpesviruses; Antiviral Agents; Herpesviridae; Human Immunodeficiency Virus (HIV); Humans; precursor; lidé; Adenoviruses, Human; activation; Viral Protease Inhibitors; HIV-1; Flavivirus; lidské adenoviry; antivirové látky; adenoviruses; Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2); Viral Proteases; inhibitory virových proteáz; Virus Diseases; protease; virové nemoci